RELATIONSHIPS BETWEEN ENERGY USE AND INCOME LEVELS, FOR HOUSEHOLDS IN GHANA - Wahib Adam, Faisal; Brew-Hammond, Abeeku; Essandoh, Eric Osei (European Scientific Journal, ESJ, 2013)
﻿﻿﻿Energy is arguably one of the major challenges the world faces today, touching all aspects of our lives. Access to energy, especially modern sources, is key to the success of any development initiative and it is important to understand the factors driving their uptake in developing countries like Ghana. According to the 2005/2006 Ghana Living Standards Survey (GLSS5) conducted by the Ghana Statistical Service,45.88% of households used electricity as the main source of lighting whilst 52.32% used kerosene, and 1.80% used gas lamps, solar, candles, generators, etc. Similarly, 55.06% used wood as their main fuel for cooking while 28.72% used charcoal, 8.94% used gas, and 7.28% of the population used other cooking fuels or did no cooking. This paper confirms the hypothesis that access to modern forms of energy increases as income levels increase. In the case of Ghana, the paper shows that the number of households using electricity as the main source of lighting increased with increasing income levels whereas kerosene had a decreasing trend. In the same vein, charcoal and gas were observed to be the fuels of choice as their usage increased with increasing income unlike wood which was observed to go down as income levels increased. Similar trends were observed at the regional level where, apart from the three northern regions, all the other regions in Ghana had a clear trend with an increasing number of households using electricity as the main source of lighting, and charcoal and gas as the main fuel for cooking, as the income quintile levels increased.